The Development of Earning Management in Indonesia: A Systematic Literature Review - Nurika Restuningdiah; Eka Ananta Sidharta (Asia Pacific Journal of Management and Education (APJME), 2023)
Earnings management is a method used by management to influence the numbers in financial statements. Earnings management is detrimental to investors because the financial statements are very low. Financial reports can no longer be trusted. Research on earnings management has been widely carried out with mixed results. Few systematic reviews have been carried out on earning management in Indonesia. The present article set out to analyze the existing literature on earning management practices in Indonesia. Guided by the ROSES or RepOrting standards for Systematic Evidence Syntheses review method, a systematic review of the Sinta 1 and 2 databases was identified with 23 related studies. Further review of these articles uses four main themes â€“ Monitoring, Management opportunities, accounting policies, and investor decision-making. Several recommendations are highlighted related to conducting more qualitative studies about earning management in different paradigms and approaches with different searching techniques such as reference searching and contacting experts.Â Keywords: earning management, Indonesia, motive, systematic literature reviewÂ